Optimizing the production schedule of an agricultural cooperative: a case study. Issue 2 (1st February 2020) - Novoa-Flores, Guido Ignacio; Carpente, Luisa; Lorenzo-Freire, Silvia
ABSTRACT: This article addresses the problem of organizing the production of livestock feed for an agricultural cooperative. The cooperative processes requests in a way that is adapted to the needs of the customers. If two requests of different composition are processed consecutively, machines must be stopped, causing loss of time, which the cooperative wishes to avoid. This article presents a mixed integer programming model that minimizes the stopping time and maximizes the free time at the end of each day. Tests with small examples demonstrate that the exact model cannot be used on real datasets owing to the complexity of the problem. For this reason, an heuristic algorithm based on the simulated annealing technique is designed. The algorithm is shown to be effective in computing high-quality solutions in a short time period.